Kinetika Sintesis Hidroksiapatit Menggunakan Metode Hidrotermal Suhu Rendah Dengan Pendekatan Shrinking Core Model - Nurul Afifah; Ahmad Fadli; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite (HA) is a ceramic that can be used as bone implants and teeth. Hydroxyapatite can be synthesized from Calcium Oxyde (CaO) commercial reacted by ammonium dihydrogen phosphate (NH4H2PO4). The purpose of this research are to determine the effect of time and temperature on characteristic of HA synthesis by low temperature hydrothermal method as well as to determine the kinetics model of HA synthesis by using the approach of shrinking core models. There are 3 models are used, the diffusion through liquid film, diffusion through HA layer, and chemical reactions. The procedure was started with synthesized 36.9 gr NH4H2PO4 was dissolved in 600 mL of water and then added 30 gr CaO with temperature of 70°C, 80°C, 90°C and reaction time of 10 minutes - 480 minutes. The mixture was stirred rate of 300 rpm until paste formed. Then the paste was dried in the oven at temperature 120°C for 12 hours and calcined at a temperature of 900oC for 1 hour. The results of this research showed that obtained products were containing 97% HA. The best of kinetic model that described HA synthesis was model of diffusion through HA layer , with formula:Keywords: hydroxyapatite, hydrothermal, CaO, kinetics model, shrinking core.